A COMPARISON BETWEEN HOLIDAY PACKAGES WITH CHARTER FLIGHT SUCEAVA – ANTALYA OF ROMANIAN TOUR OPERATORS - STANCIU, Pavel; Pitic, Adina Ionela (Revista de turism - studii și cercetări în turism, 2019)
The present work starts from the premise that since in the summer season 2019, on the tourism market in the northeast of Romania, six major tour organizers (tour operators) of holiday packages have addressed their activity explicitly to the citizens of Suceava and Botosani counties, then this niche should be treated with the utmost attention. At the same time, through a dichotomic comparison of what two of these tour operators - Kusadasi and Need Tour offer in particular, - we aimed to highlight the pluses and minuses of the most offered and, at the same time, bidder holiday packages that target Antalya destination from Turkey. The types of resorts offered, the services included in the tourist offer, the prices and tariffs applied, the Early Booking and Last Minute promotions, the booking conditions or the collaboration with the resellers agencies are all differentiated reasons regarding competition and also sources of competitive advantage. As a result, the number of tourist charter holiday packages, departing from Suceava airport, sold by Kusadasi and Need Tour during December 2018 - August 2019 was conditioned by a number of factors, many of them previously mentioned.